Studies on Schismatoglottideae (Araceae) of Borneo XXXIII - A review of the Schismatoglottis Tecturata Group, including description of a new species, Schismatoglottis evelyniae - Peter C,, Boyce; Wong Sin, Yeng (International Aroid Society Inc., 2013)
Schismatoglottis evelyniae P.C.Boyce & S.Y.Wong is described as a taxonomically new species in the Tecturata Group, morphologically most similar to Schismatoglottis platystigma M.Hotta and S. petri A. Hay. Schismatoglottis evelyniae, S. platystigma, S. petri, and S. tecturata are illustrated from living plants. A key to the species of the Schismatoglottis Tecturata Group is provided.